38(10-3.5x)=13(3x-8)+36.8

Simple and best practice solution for 38(10-3.5x)=13(3x-8)+36.8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 38(10-3.5x)=13(3x-8)+36.8 equation:


Simplifying
38(10 + -3.5x) = 13(3x + -8) + 36.8
(10 * 38 + -3.5x * 38) = 13(3x + -8) + 36.8
(380 + -133x) = 13(3x + -8) + 36.8

Reorder the terms:
380 + -133x = 13(-8 + 3x) + 36.8
380 + -133x = (-8 * 13 + 3x * 13) + 36.8
380 + -133x = (-104 + 39x) + 36.8

Reorder the terms:
380 + -133x = -104 + 36.8 + 39x

Combine like terms: -104 + 36.8 = -67.2
380 + -133x = -67.2 + 39x

Solving
380 + -133x = -67.2 + 39x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-39x' to each side of the equation.
380 + -133x + -39x = -67.2 + 39x + -39x

Combine like terms: -133x + -39x = -172x
380 + -172x = -67.2 + 39x + -39x

Combine like terms: 39x + -39x = 0
380 + -172x = -67.2 + 0
380 + -172x = -67.2

Add '-380' to each side of the equation.
380 + -380 + -172x = -67.2 + -380

Combine like terms: 380 + -380 = 0
0 + -172x = -67.2 + -380
-172x = -67.2 + -380

Combine like terms: -67.2 + -380 = -447.2
-172x = -447.2

Divide each side by '-172'.
x = 2.6

Simplifying
x = 2.6

See similar equations:

| Y=-16t^2+90t+70 | | 6x+y=4x | | 18x^3+2x^2=0 | | 6x-52=17+3x | | 2x+48=84 | | -2(3s-3)-6=-3(7s+0)-5 | | 14r-20=5r+7 | | 3(y+7.3)=11y-14.1 | | x-12y=b | | 5x-60y=a | | 4x-6=2x+20 | | 14 = f4+ 13 | | 5r-6+5r=34 | | 1/3-x/6=1/2-3x | | 3m^2+30m-75=0 | | 9a-7=17(a-3) | | 14k^2=21k | | 9(p+-6)+3=-42 | | 5(3-4x)-2(2x-3)= | | (4y^2)+8y+12x-20=0 | | -5/7y20 | | -73+2x=-10x+71 | | -33=v-17 | | -4p+35+9p=45 | | -7(x+-7)+-10=-10 | | 1=7-2z | | 12(p^2+1)=25p | | 1=7-2 | | 7(x+4)=3x+60 | | -7x-24=4 | | 15x+5x=140 | | 15c+1=160c-6 |

Equations solver categories